2018
DOI: 10.1039/c8ib00038g
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles’ functionality as redox active drugs through cytotoxicity, radical scavenging and cellular behaviour

Abstract: Targeting the oxidative stress response has recently emerged as a promising strategy for the development of therapeutic drugs for a broad spectrum of diseases. Supporting this strategy, we have reported that chitosan nanoparticles synthesized with a controlled size had selective cytotoxicity in leukemia cells through the mechanism related to reactive oxygen species (ROS) generation. Herein, we found that the cellular uptake of chitosan nanoparticles was enhanced in a time dependent manner and inhibited the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…nPLGA and nCS are considered as safe drug carriers. [24][25][26][27] This study also confirmed that CS or PLGA had no obvious cytotoxicity on periodontal membrane cells and no impact on their proliferation and may be applied for periodontal bone tissue regeneration. The safe concentration of nAg was found as 40-50 µg.…”
Section: Discussionsupporting
confidence: 72%
“…nPLGA and nCS are considered as safe drug carriers. [24][25][26][27] This study also confirmed that CS or PLGA had no obvious cytotoxicity on periodontal membrane cells and no impact on their proliferation and may be applied for periodontal bone tissue regeneration. The safe concentration of nAg was found as 40-50 µg.…”
Section: Discussionsupporting
confidence: 72%
“…One study suggested that Chit NPs had an inhibitory activity (Bor et al, 2016), two studies reported no Chit NPs effect (Omar Zaki et al, 2015;Arora et al, 2016) and three reported a stimulating effect (Hu et al, 2011;Sarangapani et al, 2018;Wang et al, 2018) on basal ROS cellular production. Concerning the polymer, same conflicting results were also found (Arora et al, 2016;Salehi et al, 2017;Sarangapani et al, 2018). From our case study, we concluded that, despite no significant differences were found in the cytotoxic profile of both NPs in RAW 264.7 cells, in ROS assay these NPs had different effects when tested at non-cytotoxic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus an 80% DDA in CH nanoparticles and polymer were able to induce ROS in a concentration-dependent manner, while a 93% DDA did not. Moreover, Sarangapani et al 81 found that with a particular size of positively charged CH nanoparticles, the oxidative stress mechanism can be triggered through ROS generation and the depletion of glutathione, becoming selectively cytotoxic for leukemia cells. Similarly, Martinez et al 60 proposed CH gold nanoparticles (CH-AuNPs) to induce ROS production as a possible treatment for cancer cells.…”
Section: Discussionmentioning
confidence: 99%